The Proximity-Concentration Tradeoff under Uncertainty - Ramondo, N.; Rappoport, V.; Ruhl, K. J. (Review of Economic Studies, 2013)
This paper analyzes the firm's choice between serving a foreign market through exports or through foreign affiliate sales in an environment characterized by country-specific shocks to the cost of production. Our model predicts that country pairs with less correlated output fluctuations trade more, relative to affiliate sales, while countries with more volatile fluctuations are served relatively more by exporters than by foreign affiliates selling abroad. Using detailed data on trade from Feenstra,